Forms and Methods of Digitalization in Russia’s Fuel and Energy Sector between XX and XXI Centuries - Igor S. Solovenko; Anatoly A. Rozhkov; Kirill A. Pinzhin; Andrey P. Zholbin (СибСкрипт)
The article offers an interdisciplinary approach to the study of digitalization in the sphere of fossil fuel business between XX and XXI centuries. This economic sector has always resisted changes, which makes the research relevant both scientifically and technologically. The authors applied the theory of modernization to analyze the key forms and methods of digitalization as part of the innovative movement in the Russian economy that took place in the early 2000s. The comparative analysis made it possible to identify the patterns behind the economic, scientific, and technical development model, including individual segments and industries. The research revealed the causes and factors that guided the processes of automation, informatization, and computerization in the domestic fuel and energy complex, also in the intersectoral context. The analysis made it possible to describe the role of the state and the business in this process. The digitalization was more active in informatization and computerization. As the scientific and technological leadership passed on from the gas industry to the oil industry, the coal mining failed to achieve technological parity by 2010. The extensive methods of implementing digital solutions, which prevailed in the 1990s and early 2000s, gave way to intensive ones. It took fuel and energy enterprises 20 years to shift from occasional automation, informatization, and computerization to a comprehensive digital transformation. The latter resulted in innovative products in other industries. As Russia’s energy security strengthened, the digital support grew more and more dependent on foreign software and hardware.